Open craniotomy surgery for subacute spontaneous subdural hemorrhage with anticoagulation therapy in cardiac arrhythmia - Achmad Adam; Bilzardy Ferry Zulkifli; Yustinus Robby Gondowardojo (Indoscholar, 2020)
Subdural hemorrhages (SDH) are an important bleeding complication of anticoagulation therapy. It’s increasing in population with the use of total anticoagulant therapy. The gold standard management for SDH is surgery. From the neurosurgery view, we cannot treat SDH and arrhythmia alone with the use of anticoagulant therapy, therefore simultaneously requires good interprofessional collaboration and teamwork. In this study, we report a further case from the neurosurgery field. A fifty-two-year-old man had a history of progressive headache, vomiting, facial asymmetries, and drowsiness resulting in a decrease of consciousness. The patient had history diagnosed with arrhythmia by a cardiologist and routinely consume anticoagulant drug therapy warfarin since three months ago. CT-scan without contrast shows isohyperdens mass with a crescent-shaped appearance at right frontotemporoparietooccipital with thickness >10 mm with midline shift >5 mm to the left. Craniotomy evacuation was performed to completely evacuate the clot instead of burrhole drainage. Further treatment is collaborated with a cardiologist to treat arrhythmia in this patient. General conditions, symptoms, and subdural thickness in this patient decide the management of surgical evacuation. Management of subdural hemorrhage with cardiac complications and the use of anticoagulant therapy requires attention because of the complication may happen. For subacute cases, usually a burrhole drainage is adequate, however, in this patient, we use open craniotomy surgery for CT-scan features consideration. Simultaneously, the anticoagulation therapy was temporarily stopped and going for further echocardiography examination. The patient underwent open craniotomy surgery, followed by good result after surgery. Further follow up to prevent rebleeding is required.